Processes affecting pollution fluxes during the coastal erosion of legacy colliery wastes - Ian T. Burke; Sebastian J. Pitman; James Hodson; Lin Niu; Fatmah Mohammed; Jenni Ilari Skakunova; Alex L. Riley; Catherine J. Gandy; Elliot Whitehead; Karen A. Hudson-Edwards; Elin Jennings; Helen Jay; et al. (Applied Geochemistry, 2026)

Exotic groundcover in an endangered grassy woodland associates with soil microbial functions that may contribute to the persistence of poor vegetation condition - Tarryn Davies; Christian Cando-Dumancela; Nicole W. Fickling; Riley J. Hodgson; Shaun Kennedy; Craig Liddicoat; Shawn D. Peddle; Sunita A. Ramesh; Alex F. Taylor; Carl D. Watson; Martin F. Breed (Applied Soil Ecology, 2026)

Uncovering UK coastal legacy wastes and their potential contaminant release risks through mineralogy and geochemistry - Patrizia Onnis; Elin Jennings; Violeta Ramos; Alex L. Riley; Catherine J. Gandy; Rich A. Crane; Ian T. Burke; Gavyn K. Rollinson; Patrick Byrne; Bryan M. Spears; Justyna P. Olszewska; Will M. Mayes; et al. (Journal of Hazardous Materials, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Speciation and leaching behaviour of inorganic contaminants in actively eroding historical coastal municipal solid waste landfills - Ian T. Burke; Patrizia Onnis; Alex L. Riley; Catherine J. Gandy; Violeta Ramos; Gavyn K. Rollinson; Patrick Byrne; Richard A. Crane; Karen A. Hudson-Edwards; Elin Jennings; William M. Mayes; J. Frederick W. Mosselmans; et al. (Marine Pollution Bulletin, 2025)

Spatially resolved source apportionment of per- and polyfluoroalkyl substances (PFAS) within a post-industrial river catchment - Patrick Byrne; William M. Mayes; Alun L. James; Sean Comber; Emma Biles; Alex L. Riley; Philip L. Verplanck; Lee Bradley (Science of The Total Environment, 2025)

Foraminifera record historical coral-algal phase shifts on Caribbean coral reefs - Akos Kalman; Alex F. Humphreys; Zach Adams; Riley Ames; Angelique R. Marín; Alex C. Dempsey; Sam J. Purkis (Marine Environmental Research, 2025)

Arid Soil Bacterial Legacies Improve Drought Resilience of the Keystone Grass, Themeda triandra - Riley J. Hodgson; Christian Cando‐Dumancela; Tarryn Davies; Victoria Drysdale; Nicole W. Fickling; Craig Liddicoat; Shawn D. Peddle; Sunita A. Ramesh; Declan Spoor; Alex Taylor; Carl Watson; Martin F. Breed (Molecular Ecology, 2025)
Plant–microbe interactions are critical to ecosystem functioning and impact soil legacies, where plants exert a lasting influence on the microbial and physicochemical conditions of the soils in which they grow. These soil legacies can affect subsequent plant growth and fitness. Specifically, biotic soil legacies can influence microbially associated plant fitness through the movement of soil microbiota in a two‐step selection process: Microbes are recruited from bulk soil into the rhizosphere (the space around roots) and then into the endosphere (within plant roots). Furthermore, these endosphere root microbiota can also influence plant behaviour, shaping bulk soil communities over time. However, the potential of these soil legacies to provide host plant drought tolerance remains poorly understood. In a drought stress greenhouse trial, we show that arid soil legacies increased the biomass of the keystone grass Themeda triandra under both drought and control conditions. We report strong positive associations between T. triandra biomass and bacterial alpha diversity across soils, rhizospheres and endospheres. These findings show that bacterial soil legacies have an important but underappreciated role in grassland species resilience to drought and could be better harnessed to support resilient grassland restoration efforts.

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

Spatial variability of metal(loid) leaching from coastal colliery wastes under freshwater and saline water conditions - Catherine J. Gandy; Ian T. Burke; Patrick Byrne; Nick Cooper; Richard A. Crane; Karen A. Hudson-Edwards; William M. Mayes; Patrizia Onnis; Alex L. Riley; Adam P. Jarvis (Journal of Environmental Management, 2025)

Spatial and temporal (annual and decadal) trends of metal(loid) concentrations and loads in an acid mine drainage-affected river - Elin Jennings; Patrizia Onnis; Rich Crane; Sean D.W. Comber; Patrick Byrne; Alex L. Riley; William M. Mayes; Adam P. Jarvis; Karen A. Hudson-Edwards (Science of The Total Environment, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Investigating the relationship between abiotic factors and the behaviour of an All-Male Nile crocodile (Crocodylus niloticus) Group - Austin Leeds; Alex Riley; Laura Stalter; Megan Terry; Andrew C. Alba; Joseph Soltis (Applied Animal Behaviour Science, 2024)

Marine heatwaves redistribute pelagic fishing fleets - Nima Farchadi; Heather Welch; Camrin D. Braun; Andrew J. Allyn; Steven J. Bograd; Stephanie Brodie; Elliott L. Hazen; Alex Kerney; Nerea Lezama‐Ochoa; Katherine E. Mills; Dylan Pugh; Riley Young‐Morse; et al. (Fish and Fisheries, 2024)
Marine heatwaves (MHWs) have measurable impacts on marine ecosystems and reliant fisheries and associated communities. However, how MHWs translate to changes in fishing opportunities and the displacement of fishing fleets remains poorly understood. Using fishing vessel tracking data from the automatic identification system (AIS), we developed vessel distribution models for two pelagic fisheries targeting highly migratory species, the U.S. Atlantic longline and Pacific troll fleets, to understand how MHW properties (intensity, size, and duration) influence core fishing grounds and fleet displacement. For both fleets, MHW size had the largest influence on fishing ground area with northern fishing grounds gaining and southern fishing grounds decreasing in area. However, fleet displacement in response to MHWs varied between coasts, as the Atlantic longline fleet displaced farther in southern regions whereas the most northern and southern regions of the Pacific troll fleet shifted farther. Characterizing fishing fleet responses to these anomalous conditions can help identify regional vulnerabilities under future extreme events and aid in supporting climate‐readiness and resilience in pelagic fisheries.

Environmental behaviour of iron and steel slags in coastal settings - Alex L. Riley; James Cameron; Ian T. Burke; Patrizia Onnis; John M. MacDonald; Catherine J. Gandy; Richard A. Crane; Patrick Byrne; Sean Comber; Adam P. Jarvis; Karen A. Hudson-Edwards; William M. Mayes (Environmental Science and Pollution Research, 2024)
Iron and steel slags have a long history of both disposal and beneficial use in the coastal zone. Despite the large volumes of slag deposited, comprehensive assessments of potential risks associated with metal(loid) leaching from iron and steel by-products are rare for coastal systems. This study provides a national-scale overview of the 14 known slag deposits in the coastal environment of Great Britain (those within 100 m of the mean high-water mark), comprising geochemical characterisation and leaching test data (using both low and high ionic strength waters) to assess potential leaching risks. The seaward facing length of slag deposits totalled at least 76 km, and are predominantly composed of blast furnace (iron-making) slags from the early to mid-20th Century. Some of these form tidal barriers and formal coastal defence structures, but larger deposits are associated with historical coastal disposal in many former areas of iron and steel production, notably the Cumbrian coast of England. Slag deposits are dominated by melilite phases (e.g. gehlenite), with evidence of secondary mineral formation (e.g. gypsum, calcite) indicative of weathering. Leaching tests typically show lower element (e.g. Ba, V, Cr, Fe) release under seawater leaching scenarios compared to deionised water, largely ascribable to the pH buffering provided by the former. Only Mn and Mo showed elevated leaching concentrations in seawater treatments, though at modest levels (<3 mg/L and 0.01 mg/L, respectively). No significant leaching of potentially ecotoxic elements such as Cr and V (mean leachate concentrations <0.006 mg/L for both) were apparent in seawater, which micro-X-Ray Absorption Near Edge Structure (μXANES) analysis show are both present in slags in low valence (and low toxicity) forms. Although there may be physical hazards posed by extensive erosion of deposits in high-energy coastlines, the data suggest seawater leaching of coastal iron and steel slags in the UK is likely to pose minimal environmental risk.

Interplay of egg white gel pH and intragastric pH: Impact on breakdown kinetics and mass transport processes - Alisha Kar; Alex G. Olenskyj; Maria Garcia Guerrero; Riley Graham; Gail M. Bornhorst (Food Research International, 2023)

Discordant population structure among rhizobium divided genomes and their legume hosts - Alex B. Riley; Michael A. Grillo; Brendan Epstein; Peter Tiffin; Katy D. Heath (Molecular Ecology, 2023)
Symbiosis often occurs between partners with distinct life history characteristics and dispersal mechanisms. Many bacterial symbionts have genomes comprising multiple replicons with distinct rates of evolution and horizontal transmission. Such differences might drive differences in population structure between hosts and symbionts and among the elements of the divided genomes of bacterial symbionts. These differences might, in turn, shape the evolution of symbiotic interactions and bacterial evolution. Here we use whole genome resequencing of a hierarchically structured sample of 191 strains of Sinorhizobium meliloti collected from 21 locations in southern Europe to characterize population structures of this bacterial symbiont, which forms a root nodule symbiosis with the host plant Medicago truncatula . S. meliloti genomes showed high local (within‐site) variation and little isolation by distance. This was particularly true for the two symbiosis elements, pSymA and pSymB, which have population structures that are similar to each other, but distinct from both the bacterial chromosome and the host plant. Given limited recombination on the chromosome, compared to the symbiosis elements, distinct population structures may result from differences in effective gene flow. Alternatively, positive or purifying selection, with little recombination, may explain distinct geographical patterns at the chromosome. Discordant population structure between hosts and symbionts indicates that geographically and genetically distinct host populations in different parts of the range might interact with genetically similar symbionts, potentially minimizing local specialization.

Palaeozoic – Early Mesozoic geological history of the Antarctic Peninsula and correlations with Patagonia: Kinematic reconstructions of the proto-Pacific margin of Gondwana - Teal R. Riley; Alex Burton-Johnson; Michael J. Flowerdew; Fernando Poblete; Paula Castillo; Francisco Hervé; Philip T. Leat; Ian L. Millar; Joaquin Bastias; Martin J. Whitehouse (Earth-Science Reviews, 2023)

Identifying dominant environmental predictors of freshwater wetland methane fluxes across diurnal to seasonal time scales - Sara H. Knox; Sheel Bansal; Gavin McNicol; Karina Schafer; Cove Sturtevant; Masahito Ueyama; Alex C. Valach; Dennis Baldocchi; Kyle Delwiche; Ankur R. Desai; Eugenie Euskirchen; Jinxun Liu; et al. (Global Change Biology, 2021)
While wetlands are the largest natural source of methane (CH 4 ) to the atmosphere, they represent a large source of uncertainty in the global CH 4 budget due to the complex biogeochemical controls on CH 4 dynamics. Here we present, to our knowledge, the first multi‐site synthesis of how predictors of CH 4 fluxes (FCH4) in freshwater wetlands vary across wetland types at diel, multiday (synoptic), and seasonal time scales. We used several statistical approaches (correlation analysis, generalized additive modeling, mutual information, and random forests) in a wavelet‐based multi‐resolution framework to assess the importance of environmental predictors, nonlinearities and lags on FCH4 across 23 eddy covariance sites. Seasonally, soil and air temperature were dominant predictors of FCH4 at sites with smaller seasonal variation in water table depth (WTD). In contrast, WTD was the dominant predictor for wetlands with smaller variations in temperature (e.g., seasonal tropical/subtropical wetlands). Changes in seasonal FCH4 lagged fluctuations in WTD by ~17 ± 11 days, and lagged air and soil temperature by median values of 8 ± 16 and 5 ± 15 days, respectively. Temperature and WTD were also dominant predictors at the multiday scale. Atmospheric pressure (PA) was another important multiday scale predictor for peat‐dominated sites, with drops in PA coinciding with synchronous releases of CH 4 . At the diel scale, synchronous relationships with latent heat flux and vapor pressure deficit suggest that physical processes controlling evaporation and boundary layer mixing exert similar controls on CH 4 volatilization, and suggest the influence of pressurized ventilation in aerenchymatous vegetation. In addition, 1‐ to 4‐h lagged relationships with ecosystem photosynthesis indicate recent carbon substrates, such as root exudates, may also control FCH4. By addressing issues of scale, asynchrony, and nonlinearity, this work improves understanding of the predictors and timing of wetland FCH4 that can inform future studies and models, and help constrain wetland CH 4 emissions.

Evaluating rural Pacific Northwest towns for wildfire evacuation vulnerability - Alex W. Dye; John B. Kim; Andrew McEvoy; Fang Fang; Karin L. Riley (Natural Hazards, 2021)

Long-term evolution of highly alkaline steel slag drainage waters - Alex L. Riley; William M. Mayes (Environmental Monitoring and Assessment, 2015)
The disposal of slag generated by the steel industry can have negative consequences upon the surrounding aquatic environment by the generation of high pH waters, leaching of potentially problematic trace metals, and rapid rates of calcite precipitation which smother benthic habitats. A 36-year dataset was collated from the long-term ambient monitoring of physicochemical parameters and elemental concentrations of samples from two steel slag leachate-affected watercourses in northern England. Waters were typified by elevated pH (>10), high alkalinity, and were rich in dissolved metals (e.g. calcium (Ca), aluminium (Al), and zinc (Zn)). Long-term trend analysis was performed upon pH, alkalinity, and Ca concentration which, in addition to Ca flux calculations, were used to highlight the longevity of pollution arising as a result of the dumping and subsequent leaching of steel slags. Declines in calcium and alkalinity have been modest over the monitoring period and not accompanied by significant declines in water pH. If the monotonic trends of decline in alkalinity and calcium continue in the largest of the receiving streams, it will be in the region of 50–80 years before calcite precipitation would be expected to be close to baseline levels, where ecological impacts would be negligible.

Thymosin β4 and Ac-SDKP: Tools to mend a broken heart - Alex Rossdeutsch; Nicola Smart; Paul R. Riley (Journal of Molecular Medicine, 2008)

Thymosin β4 and angiogenesis: modes of action and therapeutic potential - Nicola Smart; Alex Rossdeutsch; Paul R. Riley (Angiogenesis, 2007)